Developing questionnaires for students' evaluation of individual faculty's teaching skills: A Saudi Arabian pilot study - Abdullah M Al-Rubaish; Sheikh Idris Abdel Rahim; Ammar Hassan; Amein Al Ali; Fatma Mokabel; Mohammed Hegazy; Ladé Wosornu (Wolters Kluwer Medknow Publications, 2010)
Background: The National Commission for Academic Accreditation and Assessment is responsible for the academic accreditation of universities in the Kingdom of Saudi Arabia (KSA). Requirements for this include evaluation of teaching effectiveness, evidence-based conclusions, and external benchmarks. Aims: To develop a questionnaire for students' evaluation of the teaching skills of individual instructors and provide a tool for benchmarking. Setting: College of Nursing, University of Dammam [UoD], May-June 2009. Materials and Methods: The original questionnaire was "Monash Questionnaire Series on Teaching (MonQueST) - Clinical Nursing. The UoD modification retained four areas and seven responses, but reduced items from 26 to 20. Outcome measures were factor analysis and Cronbach's alpha coefficient. Results: Seven Nursing courses were studied, viz.: Fundamentals, Medical, Surgical, Psychiatric and Mental Health, Obstetrics and Gynecology, Pediatrics, and Family and Community Health. Total number of students was 74; missing data ranged from 5 to 27%. The explained variance ranged from 66.9% to 78.7%. The observed Cornbach's α coefficients ranged from 0.78 to 0.93, indicating an exceptionally high reliability. The students in the study were found to be fair and frank in their evaluation.